KONTRIBUSI PENDAPATAN USAHATANI DAN NON USAHATANI TERHADAP PENDAPATAN TOTAL KELUARGA PETANI PADI SAWAH LEBAK PINGGIRAN KOTA - Ekanovi Aktiva (JURNAL TRIAGRO, 2016)
The Contribution Income of Farmers and Non-Farmers to ward theIncome of Sawah Lebak Farmers Outside the city areas( The case of KaryaJaya Suburbdistrict of Kertapati, Palembang City).The Purpose of this research are (1). To find out the amount income of sawah lebakfarmers, (2). To find out the amount income non farmers. The income of non farmersworking as Ã¢â‚¬Å“pemulungÃ¢â‚¬Â, labourer, and so on. (3). To find out the amount contributionincome farmers and non farmers towourd the total income of sawah lebak farmers.This research is carried out at Karyajaya Suburb district of Kertapati Palembangfrom Januari 2013 up to March 2013. The location taken with consideration thatlocation is one of outside city area where most of its population are Sawah Lebak farmerand also working in sector non farmer such as pemulung, labourer at Ã¢â‚¬Å“TPAÃ¢â‚¬Â closed tofarming field area.Methode of research used al study case Sawah lebak farmer district Karya JayaKertapati Palembang as the case study. The sample taken from population as simplerandom sampling, without considering their status every body have equal right to be needas a samples.The result of research shown that the contribution family income of farmers of sawahlebak, average 47,1 % with average income Rp. 892.307,3. And Contribution income ofnon farmer family, average 52,9 % or average income Rp. 993.506 per moth. Thesemean that the activity outside farming help increase the family income of sawah lebakrice farmers at Karya Jaya district.